ANALISIS PERAN GURU KELAS DALAM MENERAPKAN PROGRAM LITERASI DASAR PESERTA DIDIK DI SD GMIT PEITOKO - Elisabet Malaikari; Antonius A. Saetban; Serly Susanti Penton (STKIP Subang, 2026)
The Basic Literacy Program is one of the efforts made by schools to improve students' reading skills and reading interests. SD GMIT Peitoko has implemented the Basic Literacy Program since 2023 through reading activities for 15 minutes before learning starts. However, the implementation of the program has not been running optimally because there are still students who are not actively participating in literacy activities, lack of teacher assistance during the activity, and limited literacy support facilities. This study aims to find out the role of classroom teachers in implementing the Basic Literacy Program at SD GMIT Peitoko. This type of research is descriptive research with a qualitative approach. Data is collected through observation, interview, and documentation techniques, then analyzed using data analysis techniques that include data reduction, data presentation, and conclusion drawn. The results of the study show that classroom teachers have played a role in implementing the Basic Literacy Program as a guide, motivator, facilitator, and evaluator. Teachers guide students in reading activities, provide motivation so that students are more active in reading, provide reading materials available at school, and make observations on the development of students' reading skills. However, the implementation of the Basic Literacy Program has not run optimally due to the lack of a collection of reading books, limited educators, and low interest and participation of students in literacy activities. Based on the results of the study, it can be concluded that classroom teachers have an important role in implementing the Basic Literacy Program at SD GMIT Peitoko. However, it is necessary to improve literacy facilities, school support, and active involvement of teachers in assisting students so that the implementation of the Basic Literacy Program can run more effectively.